2017
DOI: 10.4236/ojf.2017.72011
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Incorporating Biomass Thinning into Loblolly Pine Plantations in Alabama

Abstract: The objective of this study was to perform breakeven analysis of a stumpage biomass price that would induce landowners to modify their management regimes to incorporate an early thinning for biomass products. Following the biomass thinning, traditional harvest of pulpwood and timber products would be conducted. The feasibility analysis of incorporating biomass thinning as a potential product for a biomass market was examined for Piedmont and Coastal Plain site scenarios in Alabama. We compared our proposed bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Balancing the value of the logs obtained and the cost of precommercial thinning is always a complex issue for landowners and depends on many factors such as the availability of sawmills (determining the logistic cost for logs) or wood products manufacturers for logs of different size and quality (determining the selling prices for logs). One study for pine plantation in the southeastern U.S., more specifically Alabama, indicated that forest landowners were encouraged to practice thinning for bioenergy under favorable biomass and/or timber prices [ 73 ]. Therefore, this study included the impacts of precommercial thinning into three GCs detailed in a later section (Section “ Pine growth and yield ”) [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Balancing the value of the logs obtained and the cost of precommercial thinning is always a complex issue for landowners and depends on many factors such as the availability of sawmills (determining the logistic cost for logs) or wood products manufacturers for logs of different size and quality (determining the selling prices for logs). One study for pine plantation in the southeastern U.S., more specifically Alabama, indicated that forest landowners were encouraged to practice thinning for bioenergy under favorable biomass and/or timber prices [ 73 ]. Therefore, this study included the impacts of precommercial thinning into three GCs detailed in a later section (Section “ Pine growth and yield ”) [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…The low and high productive sites were represented by typical site indices of 60 and 90, respectively [ 97 ]. In all the cases, a high planting density of 2152 trees ha −1 was adopted to more closely reflect forest management aimed at maximizing total biomass growth [ 68 , 73 ]. While the exact thinning prescription (schedule and intensity) depends on various factors, including the goals of the landowner, the location of commercial manufacturing infrastructure, rotation age, forest health and vigor, stands are typically thinned when trees start to compete for light, moisture, and nutrition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The removal of biomass to decrease the stands overall density stocking allows trees to continue to grow at a competitive rate thereby inadvertently increasing the number of sawtimber trees available throughout the stand (Amateis et al, 2004). Planting with higher density stocking initially has also been shown to instigate greater competition between saplings encouraging straighter trees with less branches which eventually has the potential to lead to a higher quality final product (Amateis et al, 2009;Amateis and Burkhart, 2012;Gallagher et al, 2017).…”
Section: Biomass Harvestsmentioning
confidence: 99%
“…First, tract sizes are shrinking as lands become more fragmentized making it hard for landowners to find loggers willing to harvest their land (Daniel, 2012;Aguilar et al, 2014;Butler and Butler, 2016a). Next, plantations that promote woody biomass harvesting are being encourage but there are minimal markets available to sell the product to, stumpage prices are minimal if existent for the product, and today's standard sized machines aren't able to cost-effectively harvest the product so loggers aren't willing to cut the biomass for the landowner (Botard et al, 2015;BBI International, 2017;Gallagher et al, 2017;Yu et al, 2017). Finally, in order for these plantations to pay for themselves, landowners need to produce the highest sawtimber volumes possible to mitigate the risk of such a long-term investment and incentivize them to re-establish the land back into timber rather than convert it to another use that provides greater financial or intrinsic value for them (Butler and Leatherberry, 2004;Butler, 2008;Aguilar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%